Level of Physical Fitness of Elementary School Students in Class V - Ibagus Endrawan; Martinus Martinus (Yayasan Insan Mulia Bima, 2023)
The problem in this research is the lack of concentration of class V students at SDN 243 Palembang in participating in learning, developments in science and technology causing some students to be less active, and the level of physical fitness of class V students at SDN 243 Palembang is not yet known. The aim of this research was to determine the level of physical fitness of class V students at SDN 243 Palembang. This research is exploitative descriptive research. The population used in this research were 27 students at SDN 243 Palembang. This research is population research using survey methods with test and measurement techniques. The instrument used to collect data was the Indonesian Physical Fitness Test for children aged 10-12 in 2010. The data analysis technique used quantitative descriptive analysis based on Physical Fitness Norms and Indonesian Physical Fitness Levels (TKJI) Puskesjarek 2010. The research results showed that the qualification level of physical fitness fifth grade students at SDN 243 Palembang, as follows: there are 0% of students in the very good classification, 0% of students in the good classification, 81% or as many as 22 students in the medium classification, 19% or as many as 5 students in the poor classification and 0% of the students in the very little calcification. Thus, it can be concluded that the level of physical fitness of class V students at SDN 243 Palembang is in the medium category.